Penerapan Fuzzy Logic Control Pada Prototype Solar Tracker Berbasis Arduino - Mochamad Miftah; Nurjaya (CV. Multi Kreasi Media, 2024)
Solar energy is a renewable energy that can be an alternative energy that can be used for industrial and household needs. And solar energy can be converted into electrical energy. Several industries and households already use solar panels to convert solar energy and make electrical energy. However, conventional solar panels still do not get optimal results. To get optimal results, a control device using a microcontroller is needed. A microcontroller is a complete microprocessor system contained in a chip. The system is designed using the Mamdani fuzzy control method. The Mamdani method is a fuzzy inference method. The Mamdani method has the advantage of being easier to implement in a programming language and easier to understand. The control system that has been built is proven to be able to control the movement of solar panels in relation to sunlight so that it can increase the required electrical power.